PROFILE OF DEATHS BY SUICIDE IN THE FEDERAL DISTRICT, BETWEEN 2010 AND 2012. A STUDY ACCORDING TO THE LEGAL MEDICAL INSTITUTE OF THE FEDERAL DISTRICT - M. Leite, Lorena; José V. Sobrinho, Maria; Gomes de Abreu, Abraão; Andrade Almeida , Aline; de Souza Nogueira, Andressa; Rodrigues Junio, Edis; Boralli Massulini, Flavio; Gilkla da Silva Abreu, Glenya; de Ribamar de Campos Aroucha, José; Elvira de Medeiros, Luanna; Vecentin, Lyssandra; Jesus Rocha, Stael; et al. (Health and Society, 2025)
The objective of the present study was to identify the profile of deaths by suicide in the Federal District, between 2010 to 2012. It is a quantitative, descriptive study, whose data were collected in the Forensic Medicine Institute of the Federal District. The profile of deaths by suicide evidenced in the research was constituted by men, young adults, singles, with consumption of some drugs in 39.6% for both genders, being the most used the hanging, with higher incidence on Monday, day shift. The incidence of deaths was 10/100 thousand inhabitants in the evaluated period. The region showed up with the profile similar to that presented in other studies, national and international levels, drawing attention to the increase in the death rate by suicide in the DF, which almost doubled, requiring detailed analysis of the causes of this increase.